2016
DOI: 10.1038/npp.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Sex As a Biological Variable in Neuropsychiatric Research: Where Are We Now and Where Should We Be?

Abstract: Understanding the multiplicity of ways in which sex can alter the brain is essential to crafting policies and treatments that are beneficial for all human beings. This is particularly true for the field of neuropsychopharmacology, as many neuropsychiatric disorders exhibit gender bias in the frequency, severity, or response to treatment. The goal of this circumspective is to provide two views on the current state of the art of the relations between sex and the brain, relations that are studied almost exclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 40 publications
5
117
0
3
Order By: Relevance
“…In addition, there is great potential to gain mechanistic insight from studies where sex differences are identified. The antiquated myth that females are 'messy' and make research more difficult is not supported by the evidence, and articles such as this one, and those from other investigators who have been considering sex and gender in their research for decades, will help promote the inclusion and importance of SABV in biomedical research (Bale and Epperson, 2015;Miller et al, 2015;Becker and Koob, 2016;Joel and McCarthy, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, there is great potential to gain mechanistic insight from studies where sex differences are identified. The antiquated myth that females are 'messy' and make research more difficult is not supported by the evidence, and articles such as this one, and those from other investigators who have been considering sex and gender in their research for decades, will help promote the inclusion and importance of SABV in biomedical research (Bale and Epperson, 2015;Miller et al, 2015;Becker and Koob, 2016;Joel and McCarthy, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…First, as discussed in the Circumspective by McCarthy and Joel in this issue, to include SABV does not suggest that the researchers are asking nor are they powered to ask, if sex differences are present (Joel and McCarthy, 2016). Including both sexes and examining outcomes for potential differences between sexes in the results should provide insight as to whether major differences would be present and if further studies are warranted.…”
Section: Sex As a Biological Variable Tl Bale And Cn Eppersonmentioning
confidence: 99%
See 3 more Smart Citations